Do Firm Characteristics Affect Dividend Policy Differently Across Countries? Evidence from Indonesia and the Philippines - Putu Diah Kumalasari; Anik Yuesti; Ni Kadek Jelita Artha Rahma Dewi; Christian Angelo Ituriaga; Baniline Jone Abantao (Faculty of Economics and Business, Universitas Mahasaraswati Denpasar, 2026)
Purpose: This study aims to examine the determinants of dividend policy and to analyze whether their effects differ across countries, specifically between Indonesia and the Philippines. Method: The research employs a quantitative approach using secondary data from food and beverage firms listed on the Indonesia Stock Exchange (IDX) and the Philippine Stock Exchange (PSE) over the period 2022–2024, with a total sample of 69 firm-year observations. A cross-country regression model is applied by integrating data from both countries into a unified framework, incorporating a country variable and interaction terms to capture institutional differences. Findings: The results indicate that traditional firm characteristics, such as profitability, firm size, leverage, and managerial ownership do not significantly influence dividend policy. In contrast, growth opportunities have a significant negative effect, suggesting that firms with higher growth prospects tend to retain earnings rather than distribute dividends. Furthermore, the findings confirm the presence of cross-country differences, as the effects of growth opportunities and managerial ownership on dividend policy vary between Indonesia and the Philippines. Implications: This study concludes that dividend policy is not solely determined by firm-level factors but is also shaped by institutional context. However, the study is limited to the food and beverage sector and a relatively short observation period. Future research is encouraged to include broader sectors and longer time horizons.